Clinical outcomes of atezolizumab versus standard-of-care docetaxel with and without ramucirumab in patients with advanced non-small-cell lung cancer who received prior immunotherapy - Li, Shenduo; Manochakian, Rami; Chen, Ruqin; Patel, Jaydeepbhai; Inampudi, Jyothik Varun; Hiren, Koshiya R.; Zhao, Yujie; Lou, Yanyan (Frontiers in Oncology, 2024)
Background: Atezolizumab is superior to docetaxel for patients with advanced non-small-cell lung cancer (NSCLC) who are pretreated with platinum-based chemotherapy based on the POPLAR and OAK trials. However, patients who received prior immunotherapy were excluded from these trials. The standard of care second-line therapy for these patients remains to be docetaxel with or without ramucirumab. The efficacy and safety of atezolizumab as a subsequent therapy in immunotherapy-pretreated patients are unknown.We conducted a retrospective study of all patients with locally advanced or metastatic NSCLC who were pretreated with immunotherapy at Mayo Clinic Jacksonville and Rochester from 2016 to 2022. Patients who received subsequent therapy of atezolizumab alone (Atezo), docetaxel (Doce), or docetaxel + ramucirumab (Doce+Ram) were included.In this cohort of 165 patients, 12.7% (n=21), 49.1% (n=81), and 38.2% (n=63) patients received subsequent Atezo, Doce, and Doce+Ram, respectively. 1-year landmark progressionfree survival (PFS) were 23.8%, 6.2%, and 3.2% (p=0.006), and 2-year landmark PFS were 14.3%, 0%, and 0% (p<0.0001), in the Atezo, Doce, and Doce+Ram groups, respectively. About 20% patients with positive PD-L1 had durable response to atezolizumab. The Atezo group showed significantly greater overall survival (OS) improvement over Doce group (median OS 17.7 vs. 7.7 months, HR 0.47, 95% CI 0.29 -0.76, p=0.008), and over Doce+Ram group (median OS 17.7 vs. 8.9 months, HR 0.55, 95% CI 0.32 -0.95, p=0.047). 4 of 21 (19%) patients in the Atezo group developed immune-related adverse events (irAE).We observed statistically significant and clinically meaningful overall survival benefits of atezolizumab monotherapy compared with docetaxel +/-ramucirumab in patients with advanced NSCLC who were pretreated with immunotherapy. The survival benefit seems to be mainly from PD-L1 positive patients. Subsequent immunotherapy with Atezolizumab did not increase irAE rate.